PERBANDINGAN SISWA YANG DITERIMA BINA LINGKUNGAN DENGAN SISWA REGULER TERHADAP KEBUGARAN JASMANI - Abidin Daud, Muhammad Hafid; Jubaedi, Ade; Sulistianta, Heru (JUPE, 2015)
The aim of this research is to analyze the differences between the student which accepted in community development class and regular class toward physical fitness in Junior High School 9 Bandar Lampung. To collect the data the writer use quantitative methodology. The sample are the student in the grade VII and VIII which only take 10 % amount all of the student or 49 from 487 students. In collecting the data for Physical Fitness test, the writer uses the TKJI technique for 13 â 15 years old.Â Result of the test showed the student who accepted in community development class lower than in those in regular class. Based on TKJI instrumental tes, in short the percentage for physical fitness in community development reach 20,83 % whereas regular class student reach 56 %.Penelitian ini bertujuan untuk mengetahui perbandingan tingkat kebugaran jasmani siswa bina lingkungan dengan siswa reguler di SMP Negeri 9 Bandar Lampung. Metode yang digunakan dalam penelitian ini adalah metodologi penelitian kuantitatif. Sampelnya yaitu murid kelas VII dan kelas VIII di SMP N 9 Bandar Lampung yang hanya 10% dari total keseluruhan yaitu 49 anak dari 487 murid. Teknik pengambilan data untuk test Kebugaran Jasmani ini menggunakan TKJI untuk usia 13-15 tahun.Â Hasil penelitian diketahui bahwa tingkat kebugaran jasmani anak bina lingkungan lebih rendah daripada anak reguler. Pada hasil dari instrument TKJI, kebugaran jasmani kategori bina lingkungan mencapai 20,83 % sedangkan kebugaran jasmani kategori reguler mencapai 56 %.Kata kunci : bina lingkungan, kebugaran jasmani, TKJI